Variants of human DECTIN-1 rs16910526 are linked to differential reactive oxygen species production and susceptibility to tuberculosis - Cufré, Mónica (2024)
Background: Dectin-1 is a transmembrane receptor that plays a pivotal role in recognising fungi and Mycobacterium tuberculosis (Mtb). A specific variant, DECTIN-1 rs16910526, results in a truncated receptor that disrupts membrane expression and ligand binding and is clinically associated with recurrent cutaneous mycoses. Previous research has clarified the role of Dectin-1 in boosting immune defenses against mycobacteria by enhancing reactive oxygen species (ROS) production in neutrophils (PMNs). Here, we investigated the association between the rs16910526 variant and Dectin-1 expression in PMNs, as well as intracellular ROS production in response to Mtb. Furthermore, we explored the potential link between the rs16910526 gene variant and TB outcomes in Argentina. Methods: DNA was extracted from blood samples obtained from a cohort of 178 TB patients and healthy subjects (HS) in Argentina. PCR amplification and sequencing were performed to identify the rs16910526 variant. Flow cytometry was utilised to assess dectin-1 expression on the PMN plasma membrane and to measure intracellular ROS levels, as indicated by the oxidation of DHR123 in response to the Mtb antigen. Results: PMNs carrying the rs16910526 variant exhibited diminished Dectin-1 expression and ROS production in response to Mtb (p<0.0001). In a case‒control study, the rs16910526 variant had an allelic frequency of 0.112 in TB patients and 0.051 in HS. Notably, 10 out of 88 HS and 18 out of 62 TB patients harboured the variant (odds ratio [OR]: 2.55 [95% CI = 1.1–5.9, p=0.03]), indicating a potential association with TB disease. Furthermore, TB patients with the rs16910526 variant exhibited a delayed sputum smear conversion time (p<0.004) and 100% positivity for acid-fast bacilli smears (p<0.00001). Conclusion: Our study identified a significant association between the SNP variant rs16910526 in the DECTIN-1 gene and Dectin-1 expression in the PMN, leading to altered ROS production. The higher frequency of this variant in TB patients compared to HS suggests a possible link with susceptibility to TB disease in Argentina.